Evaluation of a blockchain‐based dynamic consent platform (METORY) in a decentralized and multicenter clinical trial using virtual drugs - Ki Young Huh; Seol Ju Moon; Sang‐un Jeong; Min‐Ji Kim; Wooseok Yang; Myeonggyu Jeong; Min‐Gul Kim; SeungHwan Lee (Wiley, 2022)
Abstract Blockchain is a novel data architecture characterized by a chronological sequence of blocks in a decentralized manner. We aimed to evaluate the real‐world feasibility of a blockchain‐based dynamic consent platform (METORY) in a decentralized and multicenter trial. The study consisted of three visits (i.e., screening and 2 follow‐up visits) with a 2‐week interval. Each subject was required to report the self‐measured body temperatures and take a virtual investigational drug by entering the unique drug code on the application. To simulate real‐world study settings, two major (i.e., changes in the schedule of body temperature measurement) and three minor protocol amendments (i.e., nonsignificant changes without any changes in the procedures) were set. Overall study completion rates, proportion of consent, and response time to each protocol amendment and adherence were evaluated. A total of 60 subjects (30 in each center) were enrolled in two study centers. All subjects completed the study, and the overall proportion of consent to each protocol amendment was 95.7 ± 13.7% (mean ± SD), with a median response time of 0.2 h. Overall, subjects took 90.8% ± 19.2% of the total drug, whereas compliance with the schedule was 69.1% ± 27.0%. Subjects reported 96.7% ± 4.2% of the total body temperature measurements whereas the adherence to the schedule was 59.0% ± 25.0%, which remarkably decreased after major protocol amendments. In conclusion, we evaluated a blockchain‐based dynamic consent platform in real clinical trial settings. The results suggested that major changes should be avoided unless subjects' proper understanding is warranted.